Can You Hear Me Now? Strategies to Provide Clear Health Messages to Diverse Older Adults - Chanel F. Agness; Sally E. Fletcher; Laura W. Koo; Reba Cornman (Association of American Medical Colleges, 2013)
Abstract Introduction This health communications activity was initially developed for the Geroskills Workshop, a campus-wide initiative at the University of Maryland, Baltimore campus. The workshop is offered each semester with the goals of increasing student interest in geriatrics and exposing health profession and law students to skills needed to care for older adults. The goal of this particular health communications activity is to increase student awareness of low health literacy in the geriatric population and introduce or reinforce universal strategies to facilitate clear health communication with this population. Methods The 75-minute activity is an interdisciplinary small-group discussion, a format allowing students to gain an appreciation of other professional perspectives related to the barriers and best practices of health communication. Students also learn to use different strategies based on setting and structure of the health care team. There are no prerequisites for the activity, which serves as an excellent introductory module to an entry-level didactic course or clinical rotation. Level of complexity of the discussion can easily be adjusted based on allotted time and student level of training. The activity may also be used as a refresher for health care teams currently in practice. Results This workshop has been offered not only to students but also as a continuing education presentation for health care professionals. Students filled out presenter evaluations for each session they attended at the Geroskills Workshop. Of the 30-35 students attending the health literacy session, 20 returned evaluations. Eighteen to 19 students strongly agreed that the facilitator and activity format were engaging and that the AMA video enhanced the presentation. Some students did not think 30 minutes was enough time to cover the topic (three students rated this as either neutral or disagree). Other feedback related to venue and convenience of time, which received mixed feedback (five to six students rated these areas from disagree to agree). However, compared to the high rate of agreement received for the activity, this did not seem to hamper students' ability to be engaged. Additional student comments were all positive, indicating that the topic was timely and had relevance to their current and future practice. One student expressed appreciation for the patient testimonial video: "I enjoyed the video-it really made the problem real." For the continuing education presentation, because evaluations were required for credit, there was a 98% response rate. Forty-eight evaluations were returned for the health literacy presentation. Eighty-seven percent of participants strongly agreed and the remainder agreed that the discussion was meaningful, instructive, and engaging. Nineteen percent of respondents either agreed or were neutral that 1 hour was enough time to cover the topic. One potential reason for the desire for additional time was expressed in the written comments: Several respondents would have liked to spend more time doing small-group case studies. Similar to the student feedback, additional comments from health care professionals were all positive. Several expressed a commitment to making a behavioral change after the presentation (e.g., changing their approach to patient education). Others mentioned that the discussions opened their eyes to recognizing that poor health communication among staff is an issue where they practice. The participants enjoyed the small-group, roundtable format with easy accessibility to the facilitators. Discussion This activity supports developing students' interprofessional competencies as described in the Interprofessional Education Collaborative's (IPEC's) Core Competencies for Interprofessional Collaborative Practice and in the Partnership for Health and Aging's (PHA's) Multidisciplinary Competencies in the Care of Older Adults at the Completion of the Entry-Level Health Professional Degree. The activity addresses competency domains 1, 3, and 4 of the IPEC competencies: interprofessional values and ethics related to patient-centered communication (competency domain 1), interprofessional communication (competency domain 3), and positive team dynamics through interprofessional communication and team-based problem solving using a patient case scenario (competency domain 4). The PHA expands the scope of interdisciplinary and team-care competencies to include the ability to facilitate communication with older adults and their caregivers, in addition to other members of the health care team. This patient case scenario highlights the unique health care team dynamics involved in caring for diverse older adults. Students must take the older adult's family dynamics and support systems into consideration when developing a communication strategy.